Incidental Findings in Cone-Beam Computed Tomographic Images: Calcifications in Head and Neck Region - Altındağ Ali; Avsever Hakan; Borahan Oguz; Akyol Mesut; Orhan Kaan (Balkan Stomatological Society, 2017)
Background/Aim: The use of CBCT in dentistry has been increasing popularity nowadays. CBCT images provide valuable information from anatomic structures and pathologies. Images obtained with CBCT allow for more appropriate treatment planning. The purpose of this study was to assess the calcifications which were found incidentally on CBCT images and to reveal the frequency and characteristics. Material and Methods: A total of 691 CBCT images which obtained from the patients were assessed. Demographic data and calcifications which were found out of primarily interest area were noted. The incidental findings were categorized and analyzed using descriptive statistics. Results: 945 calcifications were discovered on 318(46.02%) of the 691 patients' images. 373(53.98%) scans showed no calcificated findings. The age range of patients was from 5 to 84 years. The most common calcification was tonsillolith (86.03%), followed by stylohyoid calcifications (6.24%), antrolith and subdermal calcifications (2.33%). Conclusion: Calcified lesions in head and neck region were commonly seen in CBCT images. Although the most of the calcifications are asymptomatic and require no treatment but correct identification of these findings will reduce unnecessary further diagnostic assessments and will provide more appropriate treatment plans. It will also provide the ability comprehensively evaluation of underlying diseases and practitioners will have life-saving information by early diagnosis.